2018
DOI: 10.1016/j.apenergy.2017.10.089
|View full text |Cite
|
Sign up to set email alerts
|

Total cost of ownership and market share for hybrid and electric vehicles in the UK, US and Japan

Abstract: ReuseThis article is distributed under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs (CC BY-NC-ND) licence. This licence only allows you to download this work and share it with others as long as you credit the authors, but you can't change the article in any way or use it commercially. More information and the full terms of the licence here: https://creativecommons.org/licenses/ TakedownIf you consider content in White Rose Research Online to be in breach of UK law, please notify us by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
162
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 368 publications
(171 citation statements)
references
References 32 publications
5
162
0
4
Order By: Relevance
“…Palmer et al. provide an extensive assessment of the TCO of conventional, hybrid, plug‐in hybrid and battery electric vehicles in three industrialized countries (UK, USA‐using California and Texas as case studies, and Japan) for time period 1997–2015, stressing the importance of financial subsidies for EVs, as well as non‐financial incentives. Moreover, this paper provides a review of five studies on TCO, showing the major differences in assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmer et al. provide an extensive assessment of the TCO of conventional, hybrid, plug‐in hybrid and battery electric vehicles in three industrialized countries (UK, USA‐using California and Texas as case studies, and Japan) for time period 1997–2015, stressing the importance of financial subsidies for EVs, as well as non‐financial incentives. Moreover, this paper provides a review of five studies on TCO, showing the major differences in assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of previously published papers considered vehicle ownership costs in just one country or one geographic region (e.g., Gilmore and Patwardhan [19] consider passenger vehicle TCO in India, and Diao et al [20] look at private car TCO in China). Palmer et al [21] provide an extensive assessment of the TCO of conventional, hybrid, plug-in hybrid and battery electric vehicles in three industrialized countries (UK, USA-using California and Texas as case studies, and Japan) for time period 1997-2015, stressing the importance of financial subsidies for EVs, as well as non-financial incentives. Moreover, this paper provides a review of five studies on TCO, showing the major differences in assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in this case, it is suggested that autonomous EVs produce dramatically fewer emissions than gasoline AVs (Gawron et al, 2018) and consume fewer energy (Vahidi and Sciarretta, 2018). Third, EVs are technically and economically beneficial rather for longer daily travel distances experienced by shared fleets due to their relatively low maintenance needs (Logtenberg et al, 2018;Palmer et al, 2018;Weldon et al, 2018). However, despite the aforementioned advantages, configuration of a shared service based on EVs meets some operational concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasingly strict pollutant emissions and fuel economy standards have led the performance improvement of ground vehicles employing alternative energy to become a hot topic . Hybrid electric vehicles (HEVs) are regarded as one of the most crucial solutions to enhance the fuel economy of automobiles because they can decrease fuel consumption and exhaust emissions by utilizing electric energy with the low cost and pollution‐free advantages …”
Section: Introductionmentioning
confidence: 99%
“…1,2 Hybrid electric vehicles (HEVs) are regarded as one of the most crucial solutions to enhance the fuel economy of automobiles because they can decrease fuel consumption and exhaust emissions by utilizing electric energy with the low cost and pollution-free advantages. [3][4][5] The design of powertrain configuration is the key part of the design of hybrid electric vehicles. Configuration determines the power flow path and the coupling method of the power sources, which contributes to distinct difference of fuel economy and dynamic performance between hybrid electric vehicles equipped with various configurations.…”
Section: Introductionmentioning
confidence: 99%